2023
DOI: 10.3390/economies11010030
|View full text |Cite
|
Sign up to set email alerts
|

Bank Market Structure and SMMEs’ Access to Finance: A South African Perspective

Abstract: While the importance of the banking sector on various fundamental economic variables is well-documented in the literature, little is known about the relationship between the bank market structure and access to finance for opaque firms, particularly in developing economies such as South Africa. Using ordered probit and logit models, we investigate the impact of bank market structure on small, micro and medium enterprises (SMMEs)access to finance. Our results show that high bank concentration increases the obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The lack of a will to improve creates an environment whereby SMMEs are on the peripheries of the township, reflecting poor readiness to adopt the 4IR in all aspects. This is in line with the conclusion by Ngonisa et al (2023) that SMMEs' access to finance is determined by location heterogeneity. Financial factors were highlighted as the most influential reason for adopting the latest ICT applications used by similar SMMEs.…”
Section: The Readiness Of Smmes To Adopt the Fourth Industrial Revolu...supporting
confidence: 91%
See 2 more Smart Citations
“…The lack of a will to improve creates an environment whereby SMMEs are on the peripheries of the township, reflecting poor readiness to adopt the 4IR in all aspects. This is in line with the conclusion by Ngonisa et al (2023) that SMMEs' access to finance is determined by location heterogeneity. Financial factors were highlighted as the most influential reason for adopting the latest ICT applications used by similar SMMEs.…”
Section: The Readiness Of Smmes To Adopt the Fourth Industrial Revolu...supporting
confidence: 91%
“…This was confirmed by Pu, Qamruzzaman, Mehta, Naqvi, and Karim (2021), who found that a lack of money, a lack of networking opportunities, and a lack of government backing are the main obstacles to the expansion of SMMEs. Ngonisa et al (2023) mentioned that evidence reveals that most SMMEs fail as a result of a lack of access to finance, with between 70% and 80% of the SMMEs closing before they reach five years of operation. It was suggested that to improve access to finance by SMMEs, policymakers should focus on policies that seek to enhance high competition in the banking sector (Ngonisa et al, 2023).…”
Section: External Support Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this comprehensive literature review underscore the pivotal role played by Small, Medium, and Micro Enterprises (SMMEs) in South Africa's economic landscape (TeSai, 2014;Dalberg, 2011;Yoshino and Taghizadeh-Hesary, 2020;Ngonisa et al, 2023). These enterprises emerge as integral drivers of sustainable development and job creation, addressing the pressing issues of unemployment, inequality, and poverty.…”
Section: Implications For Smmesmentioning
confidence: 96%
“…Established SMMEs may be unable to purchase raw materials, access skilled labour, infrastructure, distribution, and transport logistics, or secure the necessary expertise to expand or survive during adverse conditions. This could limit growth and competitiveness (Nkwabi and Mboya, 2019;Mini, 2017;Ngonisa et al, 2023). The challenge that continues to exist is that SMMEs may (theoretically) get financing from a wide variety of sources, including the government and the private sector which may assist SMMEs to grow, including tax breaks, grants, equity financing alternatives, and loans.…”
Section: Access To Capitalmentioning
confidence: 99%